Associação entre perdas precoces de implantes dentários e polimorfismos genéticos de IL-8, IL-17 e IL-23 - Gonçalves Filho, Raimundo Thompson (2019)
Osseointegrated implants are the treatment of choice to replace dental losses. Despite its high rate of success, some patients have failed the normal process of osseointegration. The complexity of finding the etiology for implant losses in those cases where all other possible factors have been carefully controlled is still a challenge. The identification of the predisposition of the patient to this type of event through the integrated analysis that associates genetic polymorphisms of the host and analysis of the level of gene expression, opens new diagnostic possibilities. The aim of this study was to verify the association of polymorphisms in genes related to the inflammatory response IL-17 7488 A / G, IL-23 2199 A / C and IL-8 251 A/T in implant failure. Materials and Methods: A total of 86 patients who underwent dental implant surgery were divided into two groups: a test group composed of 25 patients who lost 1 (um) or more implants after the normal osseointegration and control group composed of 61 patients who did not lose any implants installed. The genotyping of polymorphisms in the interleukin genes studied was performed through the analysis of the genomic DNA obtained from the peripheral blood, using the PCR-RFLP (restriction fragment length polymorphism) technique. The significance of the differences in allele frequencies and genotypes of the polymorphisms were assessed using the chi-square test (p <0.05) and the odds ratio was calculated. No significant differences were observed in the distribution of alleles and genotypes of polymorphisms when the two groups were compared. In the multinomial logistic regression model the failure of implants did not show a strong association with IL-17 and IL-23 polymorphisms, however, the IL-8 gene polymorphism increased by 1.82 (95% CI = 0.61-5, 45) times the risk of implant failure. The results indicate that polymorphisms in IL-17 7488 A / G, IL-23 2199 A / C and IL-8 251 A/T interleukin genes are not associated with early implant failure, suggesting that the presence of these single nucleotide polymorphisms does not constitute a genetic risk factor for the loss of implants in the study population.